2010
DOI: 10.1007/s10750-010-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

Birds as eutrophicating agents: a nutrient budget for a small lake in a protected area

Abstract: Sources of nitrogen and phosphorus were measured for a small pool, Brown Moss, which is a Site of Special Scientific Interest in the UK. The site is designated for its macrophyte and bird interest and comprises several pools flanked by heath and woodland. Currently the largest pool has high mean concentrations of total N and P (4 ± 2.4 mg N l -1 and 389 ± 254 lg P l -1 ), and also suffers from water table fluctuation and recreational impact. There are no point sources of nutrients but potential diffuse sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Bird impact without food quality (q = 1, grey lines) is shown for comparison. At a density of 50 coots ha -1 , macrophytes were not present for any of the P loadings Hydrobiologia (2016) 777:197-207 203 droppings, thereby contributing to eutrophication directly (Hahn et al, 2008;Chaichana et al, 2010). Another mechanism by which the impact of coots could be larger than predicted by PCLake is nonconsumptive destruction of macrophytes while foraging on invertebrates (Paillisson & Marion, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Bird impact without food quality (q = 1, grey lines) is shown for comparison. At a density of 50 coots ha -1 , macrophytes were not present for any of the P loadings Hydrobiologia (2016) 777:197-207 203 droppings, thereby contributing to eutrophication directly (Hahn et al, 2008;Chaichana et al, 2010). Another mechanism by which the impact of coots could be larger than predicted by PCLake is nonconsumptive destruction of macrophytes while foraging on invertebrates (Paillisson & Marion, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The capacity for waterfowl to serve as nutrient vectors has been studied across a variety of aquatic habitats (Chaichana et al 2010;Manny et al 1994;Olson et al 2005;Post et al 1998). Waterfowl at Lake Mattamuskeet, particularly Snow Goose (Chen caerulescens) and Tundra Swan (Cygnus columbianus), feed in adjacent wetland or agricultural habitats, but return to the Lake to roost where their defecation represents an allochthonous source of N. While we lack highresolution quantitative data on the movement of all species of waterfowl, we observed a consistent daily influx of geese, Tundra Swan, and ducks into the lake and impoundments at dusk.…”
Section: Bird Transportmentioning
confidence: 99%
“…We found that dense congregation of waterfowl, mainly Canada geese, raised ammonium concentrations in pool 6 in winter 2004 (Chaichana et al, 2010). Solid wastes excreted by water birds in winter may subsequently affect water chemistry in summer as they decompose.…”
Section: Water Quality and Nutrient Sources And Movementsmentioning
confidence: 81%
“…Solid wastes excreted by water birds in winter may subsequently affect water chemistry in summer as they decompose. Nutrient budgets for pool 6 showed substantial release of phosphorus and ammonium from the sediments in summer and birds were the major external loading source of phosphorus (Chaichana et al, 2010). This effect is unlikely to extend to other pools as there were much greater species numbers and densities of waterfowl on pool 6 than in the smaller pools 3 and 14.…”
Section: Water Quality and Nutrient Sources And Movementsmentioning
confidence: 92%
See 1 more Smart Citation